Unveiling the Morphology of Saharan Heritage: Exploring Urban Heritage in the Algerian Sahara - Gherraz, Halima; Guechi, Imen; Alkama, Djamel (Future Science, 2023)
This study is dedicated to exploring the Ksurian heritage of the Algerian Sahara, aiming to reveal the abundance and variety embedded within each ksar. Employing a comprehensive analytical approach, we meticulously examine four fundamental aspects: the urban layout, the dwellings, the materials utilized, and the construction techniques employed. To accomplish this research, extensive field visits were conducted, encompassing photography, on-site surveys, and engaging discussions with experts to gain profound insights into the distinctive characteristics of each region. Our findings unveil a remarkable and diverse heritage, exhibiting variations from one region to another, ultimately reflecting the unique traditions and capabilities of the Saharan population.